Establishment of a WHO Reference Reagent for anti-Mullerian hormone - Jackie Ferguson; Jason Hockley; Peter Rigsby; Chris Burns (BMC, 2020)
Abstract Background There is a need for a reference material to support the development and ensure the quality of immunoassays for human AMH. A batch of ampoules, coded 16/190, containing lyophilised recombinant AMH was evaluated in a WHO Collaborative Study. The aims of the study were to determine the AMH content in terms of the calibration of each immunoassay method, to predict long-term stability and to assess the suitability of the preparation to calibrate AMH immunoassays. Methods Study participants were asked to report the AMH content of specific dilutions of coded ampoules of 16/190 and a comparator preparation containing approximately half the AMH content. In each assay, participants also reported the AMH content of 22 patient samples to assess commutability. A robust all-laboratory geometric mean of the content estimates was determined using the laboratory geometric mean estimates. Commutability was assessed using a difference in bias approach. Stability was predicted by the measurement of thermally accelerated degradation samples. Results Seven laboratories performed twenty-one immunoassay method-platform combinations, sixteen of which provided data which met the validity criteria, giving a consensus geometric mean estimate of AMH content of 511 ng/ampoule (95% CI, 426-612, n = 16, GCV 42%) and a robust geometric mean of 489 ng/ampoule. By contrast, the GCV% for the all-laboratory geometric mean of the relative content estimates for the comparator sample to 16/190 was 12%. Commutability was assessed using 20 of the 22 representative patient samples. Of the valid assays, 16/190 was within the limits of acceptable commutability for 6 methods, partially commutable for a further 3 methods and non-commutable when measured by 7 methods. The preparation was predicted to be highly stable when stored at − 20 °C. Conclusion The majority of methods met the validity criteria. Content estimates showed a high between-method variability, yet assays exhibited a similar proportionality of response as demonstrated using the comparator sample. 16/190 was commutable in some but not all methods. On the basis of these results, it was agreed by the WHO Expert Committee on Biological Standardization to establish 16/190 as a WHO Reference Reagent for AMH with a content defined by consensus immunoassay of 489 ng/ampoule.